2010
DOI: 10.1093/ndt/gfq067
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypernatraemia acquired in the ICU and mortality: a cohort study

Abstract: IAH is frequent and associated with mortality after adjustment on severity at ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
138
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 29 publications
11
138
2
6
Order By: Relevance
“…We found that 9.9% of admissions were associated with hypernatremia, an incidence similar to prior estimates of 1.3–9% in other populations using a similar definition of hypernatremia [1,2,3,20,21,22,23]. The wide range in these estimates is a reflection of the different populations studied.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that 9.9% of admissions were associated with hypernatremia, an incidence similar to prior estimates of 1.3–9% in other populations using a similar definition of hypernatremia [1,2,3,20,21,22,23]. The wide range in these estimates is a reflection of the different populations studied.…”
Section: Discussionsupporting
confidence: 83%
“…Other multivariate analyses demonstrating an association of hypernatremia with mortality have used different methods for correcting for renal function. One study examined the Simplified Acute Physiology Score II and the Logistic Organ Dysfunction score at admission [21]. While this study accounted for chronic kidney disease at admission, the only variable that included AKI during the hospital course was the need for RRT.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study reported increasing mortality risk ratios of 2.32 and 3.64 in patients with mild (>150, ≤155 mEq/L) and severe (>155 mEq/L) hypernatremia. 13 It is therefore essential to prevent the onset of hypernatremia in patients treated with tolvaptan, which may cause hypernatremia event because of its aquaretic effect.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas some authors have defined hypernatremia as serum sodium ≥ 146 mEq/L, 5,18 or ≥ 150 mEq/L, 2,14,17 we chose to classify hypernatremia into mild, moderate, and severe, as described previously. 2,11 This categorization is especially important for patients with TBI, …”
Section: Discussionmentioning
confidence: 99%